Menggereja Bersama Pemulung - Gresela Maimina; Defi Stenly Nenkeula; Margie Maatoke; Veronike Mailao (Program Pascasarjana UKIM, 2024)
This research aims to analyze the reality of the lives of scavengers, the problem of poverty that holds them hostage, and the role of the church in empowering scavengers. The scavenger profession is carried out due to the acute poverty problem experienced by urban communities. Scavengers work by picking up rubbish, such as aqua glass, bottles, iron, and various other rubbish that can be sold, to meet economic needs. Scavengers are always viewed negatively as poor people and often receive discrimination from society in general. Using qualitative research methods, this research conducted observations and in-depth interviews with scavengers to reveal the realities and life experiences of scavengers. Next, descriptive analysis was carried out to show the role and involvement of the church in empowering scavengers. This article finds that the presence of the church today is no longer just a ritual presence, but a presence that empowers people to face various social problems, such as poverty experienced by scavengers. This research offers a concept of churching with scavengers which emphasizes the church's mission to empower scavengers in facing the problem of poverty that binds them.